Math, asked by parikshit16, 1 year ago

simplify (2√5+3√2)² +(2√5-3√2)²​

Answers

Answered by pinquancaro
2

Answer:

(2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2=76

Step-by-step explanation:

Given : Expression (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2

To find : Simplify the expression ?

Solution :

Expression (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2

Open the squaring term by identity, (a+b)^2=a^2+b^2+2ab

=(2\sqrt5)^2+(3\sqrt2)^2+2(2\sqrt5)(3\sqrt2)+(2\sqrt5)^2+(3\sqrt2)^2-2(2\sqrt5)(3\sqrt2)

Cancel the like terms,

=20+18+20+18

=40+36

=76

Therefore, (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2=76

Answered by harendrachoubay
1

The value of the (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2 is equal to 76.

Step-by-step explanation:

We have,

(2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2

To find, the value of the (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2 = ?

(2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2

Here, a = 2\sqrt5 and b = 3\sqrt2

We know that,

The algebraic identity,

(a+b)^2 +(a-b)^2=2(a^2+b^2)

(2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2

=2[(2\sqrt5)^2+(3\sqrt2)^2]

= 2[4(5) + 9(2)]

= 2(20 + 18)

= 2(38)

= 76

∴ The value of the (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2 = 76

Thus, the value of the (2\sqrt5+3\sqrt2)^2+(2\sqrt5-3\sqrt2)^2 is equal to 76.

Similar questions